Can Combining Performance-Based Financing With Equity Measures Result in Greater Equity in Utilization of Maternal Care Services? Evidence From Burkina Faso - Takondwa Mwase; Julia Lohmann; Saidou Hamadou; Stephan Brenner; Serge M.A. Somda; Hervé Hien; Michael Hillebrecht; Manuela De Allegri (Kerman University of Medical Sciences, 2022)
BackgroundAs countries reform health financing systems towards universal health coverage, increasing concerns emerge on the need to ensure inclusion of the most vulnerable segments of society, working to counteract existing inequities in service coverage. To this end, selected countries in sub-Saharan Africa have decided to couple performance-based financing (PBF) with demand-side equity measures. Still, evidence on the equity impacts of these more complex PBF models is largely lacking. We aimed at filling this gap in knowledge by assessing the equity impact of PBF combined with equity measures on utilization of maternal health services in Burkina Faso. MethodsOur study took place in 24 districts in rural Burkina Faso. We implemented an experimental design (cluster-randomized trial) nested within a quasi-experimental one (pre- and post-test design with independent controls). Our analysis relied on self-reported data on pregnancy history from 9999 (baseline) and 11 010 (endline) women of reproductive age (15-49 years) on use of maternal healthcare and reproductive health services, and estimated effects using a difference-in-differences (DID) approach, purposely focused on identifying program effects among the poorest wealth quintile.ResultsPBF improved the utilization of few selected maternal health services compared to status quo service provision. These benefits, however, were not accrued by the poorest 20%, but rather by the other quintiles. PBF combined with equity measures did not produce better or more equitable results than standard PBF, with specific differences only on selected outcomes. ConclusionOur findings challenge the notion that implementing equity measures alongside PBF is sufficient to produce an equitable distribution in program benefits and point at the need to identify more innovative and context-sensitive measures to ensure adequate access to care for the poorest. Our findings also highlight the importance of considering changing policy environments and the need to assess interferences across policies.